(untitled) (Current Horticulture, 2024)
An integrated protocol was standardized for production of diversified products from strawberry (Fragaria x ananassa). The fresh fruits were subjected to lactic acid fermentation using Lactobacillus sp. The prepared probiotic drink was collected and left over fruits were utilized for preparation of other products, viz. candy, squash, jelly and wine. Candy was prepared by incubating whole fruits in subsequently increasing concentrations of sugar syrup and then drying at 60 oC temperature in electric dehydrator to an intermediate moisture level of around 12%. The sugar syrup thus left had attractive red color due to anthocyanins extracted from the fruits. It was used for preparation of squash, jelly and wine. The strawberry probiotic drink contained 2.2 oB TSS, 0.17% acidity, 2.1 mg/100ml vitamin-C, 37.1 mg/100ml phenolics and 2.36 mg/100ml anthocyanins. During ambient storage of probiotic drink up to 30 days, vitamin-C, phenolics and anthocyanin contents decreased while reducing sugars increased. Quality analysis of strawberry products revealed that candy contained highest amounts of phenolics and anthocyanins followed by jam, jellly and squash and least in wine. The vitamin-C content ranged between 1.6 to 14.8 mg/100 g or ml, being highest in jelly while least in wine. The ethanol content in wine was found to be 11.7 per cent. All the strawberry products were highly acceptable during sensory evaluation scoring above 7.0 out of total 9.0. It may be concluded that a variety of processed products could be prepared from same raw material by using the integrated protocol for strawberry products.